PAMELA's measurements of geomagnetic cutoff variations during the 14 December 2006 storm. Issue 3 (11th March 2016) - Adriani, O.; Barbarino, G. C.; Bazilevskaya, G. A.; Bellotti, R.; Boezio, M.; Bogomolov, E. A.; Bongi, M.; Bonvicini, V.; Bottai, S.; Bruno, A.; Cafagna, F.; Campana, D.; et al.
Abstract: Data from the Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics (PAMELA) satellite experiment were used to measure the geomagnetic cutoff for high‐energy (≳ 80MeV) protons during the 14 December 2006 geomagnetic storm. The variations of the cutoff latitude as a function of rigidity were studied on relatively short timescales, corresponding to spacecraft orbital periods (∼94 min). Estimated cutoff values were compared with those obtained by means of a trajectory‐tracing approach based on a dynamical empirical modeling of the Earth's magnetosphere. We found significant variations in the cutoff latitude, with a maximum suppression of ∼7° at lowest rigidities during the main phase of the storm. The observed reduction in the geomagnetic shielding and its temporal evolution were related to the changes in the magnetospheric configuration, investigating the role of interplanetary magnetic field, solar wind, and geomagnetic parameters. PAMELA's results represent the first direct measurement of geomagnetic cutoffs for protons with kinetic energies in the sub‐GeV and GeV region. Key Points: Direct measurement of high‐energy proton cutoffs during the 14 December 2006 magnetospheric storm Significant reduction in the geomagnetic shielding observed, with a 7 degree maximum suppression Cutoff changes well correlated with the IMF strength, its Z component, SYM‐H, and, especially, Kp